Basic concepts of Chemistry - Malone, Leo J. (John Wiley & Sons, 2004)
In photochemical reactions, such as photosynthesis, light energy initiates a chemical reaction. In the jellyfish we have just the opposite situation. That is, light energy is produced by a chemical reaction. The production of light energy by a chemical reaction is known as chemiluminescence. If it is produced by living organisms, such as the jellyfish, it is known as bioluminescence. This text emphasizes the relevance of chemistry to the world around us. Both within the text and in the essays entitled "Making It Real" you will find discussions of how the abstract subject of chemistry relates to the reality of our everyday lives. The Making It Real essay in Chapter 13 discusses bioluminescence that was first noticed in fireflies.